A holistic approach to safe and eco-friendly driving in Indonesia from prospective psychology and technology: Literature-based exploration - Suryati Mahdalena Sianipar; Charli Sitinjak; Daniel Handoko (Psycho Holistic, 2024)
Transportation is essential to daily life in Indonesia, supporting mobility, economic activity, and social connectivity. However, rapid urbanization and population growth have intensified challenges, including severe traffic congestion, high accident rates, and substantial contributions to carbon emissions. Traditional approaches to transportation management have proven insufficient to address these issues. This study aims to explore the role of psychological insights and technological advancements in fostering safer and more sustainable driving practices in Indonesia through a literature-based exploration. Data collection involved a structured review of academic publications, reports, and case studies published between 2010 and 2023, accessed from sources such as Scopus, Google Scholar, and institutional archives. Relevant studies were identified using keywords like "safe driving," "psychology of driver behavior," and "sustainable transportation technologies. “The findings emphasize that psychological factors—such as motivation, risk perception, and emotional regulation—play a pivotal role in influencing driver behavior. In parallel, technologies like Advanced Driver Assistance Systems (ADAS) and eco-driving innovations offer practical solutions to enhance safety and reduce environmental impacts. The synergy between psychological understanding and technological applications creates a comprehensive framework for addressing Indonesia’s unique transportation challenges. This review identifies significant research gaps, such as the limited integration of behavioral insights with technology adoption in Indonesian contexts. The study recommends tailored interventions, such as psychology-informed driver training programs and localized promotion of adaptive driving technologies, to improve transportation safety and sustainability outcomes.